Number of Pain Locations as a Predictor of Cause-Specific Disability Pension in Sweden-Do Common Mental Disorders Play a Role?. Issue 8 (August 2019) - Ropponen, Annina; Narusyte, Jurgita; Mittendorfer-Rutz, Ellenor; Svedberg, Pia
Abstract : Objective: The aim of this study was to investigate the associations between number of pain locations, common mental disorders (CMDs), and disability pension (DP). Methods: Survey data in 1998 to 2003 for 27, 165 Swedish twins born in 1935 to 1958 were linked to national DP data until 2013. Pain locations were evaluated for back, low back, sciatica, shoulder, or neck pain, and CMDs for lifetime major depression and 1-month anxiety. Results: The number of pain locations was associated with DP in a dose–response manner. One pain location had a hazard ratio of 1.50 (95% confidence interval 1.35 to 1.68) and five pain locations hazard ratio 4.67 (95% confidence interval 4.11 to 5.30) for DP. Also, CMDs were associated with DP. Conclusion: The number of pain locations has a dose–response association with the risk of DP. CMDs predict DP. In strategies to prevent DP, early signs of pain or CMDs should be taken into consideration.